2018
DOI: 10.29036/jots.v9i17.25
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Perceived Crowding, and Atmospherics on Visitor Satisfaction at Cultural Heritage Sites: A Comparison of Turkish and British Visitors to Topkapi Palace, Istanbul

Abstract: Cultural heritage sites impress the visitors by their ‘worth-to-see’ architectural characteristics and historical or cultural importance. Visitor experiences at cultural areas are also influenced by site atmospherics, and crowd, that form visitors’ overall satisfaction with the site. This study aims to examine the relationships amongst visitors’ crowding, and atmospherics perceptions, and overall satisfactions in a cultural tourism area. With this purpose, a survey was conducted at one of the most popular heri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…The previous studies dealing with the visitor experience in the existing museum and tourism literature (Dierking & Falk, 1992;Falk, 2009;Chan & Yeoh, 2010;Dirsehan, 2011;Alelis et al, 2013;Allan & Altal, 2016;Geiling & Ong, 2016;Çetinsöz, 2017;Kaygusuz, 2017;Kılıçarslan & Caber, 2018) evaluate the experience with other subjects or discipline. For instance, they try to explain the visitor's experience with the subjects like atmosphere, and physical facilities of a museum, new technologies or with disciplines like marketing, aesthetic, education.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies dealing with the visitor experience in the existing museum and tourism literature (Dierking & Falk, 1992;Falk, 2009;Chan & Yeoh, 2010;Dirsehan, 2011;Alelis et al, 2013;Allan & Altal, 2016;Geiling & Ong, 2016;Çetinsöz, 2017;Kaygusuz, 2017;Kılıçarslan & Caber, 2018) evaluate the experience with other subjects or discipline. For instance, they try to explain the visitor's experience with the subjects like atmosphere, and physical facilities of a museum, new technologies or with disciplines like marketing, aesthetic, education.…”
Section: Discussionmentioning
confidence: 99%
“…Neuts and Nijkamp [ 23 ] developed a crowding perception model by examining the destination environment in Bruges. Liu and Ma [ 24 ] discovered that the perception of crowdedness is not directly related to tourist satisfaction, while Kılıçarslan and Caber [ 25 ] reported contradicting results. Notably, since the nature of service offerings and atmosphere vary among different sites, Koens et al [ 2 ] made recommendations to analyze the effects of overtourism based on specific attractions rather than the whole destination.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Personal or group standards may differ, and studies have identified various determinants of groups' and individuals' perception of crowding. Several studies show that nationality influences perception of crowding (see e.g., Jin et al 2016, Kiliçarslan and Caber 2018, Sayan et al 2013, Sun and Budruk 2017. Cultural differences are seen as the main reasons for these differences (Sayan et al 2013).…”
Section: Determinants Of Perception Of Crowdingmentioning
confidence: 99%
“…Congestion and perceived crowding can limit tourists' ability to engage in desired activities, lead to undesired social contacts and stimulus overload (Kiliçarslan andCaber 2018, p. 58, Sanz-Blas et al 2019). Due to the potential negative impacts of crowding on the visitor experience, crowding is an important element in visitor satisfaction.…”
Section: Crowding and Visitor Satisfactionmentioning
confidence: 99%